2.2.57 Problems 5601 to 5700

Table 2.115: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

5601

\[ {}{y^{\prime }}^{3}-2 y y^{\prime }+y^{2} = 0 \]

[_quadrature]

1.849

5602

\[ {}{y^{\prime }}^{3}-a x y y^{\prime }+2 a y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries]]

8.691

5603

\[ {}{y^{\prime }}^{3}-x y^{4} y^{\prime }-y^{5} = 0 \]

[[_1st_order, _with_linear_symmetries]]

10.617

5604

\[ {}{y^{\prime }}^{3}+{\mathrm e}^{3 x -2 y} \left (y^{\prime }-1\right ) = 0 \]

[[_homogeneous, ‘class C‘], _dAlembert]

1.029

5605

\[ {}{y^{\prime }}^{3}+{\mathrm e}^{-2 y} \left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x -2 y} = 0 \]

[‘y=_G(x,y’)‘]

504.072

5606

\[ {}{y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0 \]

[_quadrature]

100.839

5607

\[ {}{y^{\prime }}^{3}-{y^{\prime }}^{2}+y^{2} = 0 \]

[_quadrature]

35.214

5608

\[ {}{y^{\prime }}^{3}-{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

0.671

5609

\[ {}{y^{\prime }}^{3}-a {y^{\prime }}^{2}+b y+a b x = 0 \]

[[_homogeneous, ‘class C‘], _dAlembert]

1.116

5610

\[ {}{y^{\prime }}^{3}+\operatorname {a0} {y^{\prime }}^{2}+\operatorname {a1} y^{\prime }+\operatorname {a2} +\operatorname {a3} y = 0 \]

[_quadrature]

142.629

5611

\[ {}{y^{\prime }}^{3}+\left (1-3 x \right ) {y^{\prime }}^{2}-x \left (1-3 x \right ) y^{\prime }-1-x^{3} = 0 \]

[_quadrature]

0.693

5612

\[ {}{y^{\prime }}^{3}-y {y^{\prime }}^{2}+y^{2} = 0 \]

[_quadrature]

2.363

5613

\[ {}{y^{\prime }}^{3}+\left (\cos \left (x \right ) \cot \left (x \right )-y\right ) {y^{\prime }}^{2}-\left (1+y \cos \left (x \right ) \cot \left (x \right )\right ) y^{\prime }+y = 0 \]

[_quadrature]

1.801

5614

\[ {}{y^{\prime }}^{3}+\left (2 x -y^{2}\right ) {y^{\prime }}^{2}-2 x y^{2} y^{\prime } = 0 \]

[_quadrature]

2.323

5615

\[ {}{y^{\prime }}^{3}-\left (2 x +y^{2}\right ) {y^{\prime }}^{2}+\left (x^{2}-y^{2}+2 x y^{2}\right ) y^{\prime }-\left (x^{2}-y^{2}\right ) y^{2} = 0 \]

[_quadrature]

3.356

5616

\[ {}{y^{\prime }}^{3}-\left (x^{2}+x y+y^{2}\right ) {y^{\prime }}^{2}+x y \left (x^{2}+x y+y^{2}\right ) y^{\prime }-x^{3} y^{3} = 0 \]

[_quadrature]

3.204

5617

\[ {}{y^{\prime }}^{3}-\left (x^{2}+x y^{2}+y^{4}\right ) {y^{\prime }}^{2}+x y^{2} \left (x^{2}+x y^{2}+y^{4}\right ) y^{\prime }-x^{3} y^{6} = 0 \]

[_quadrature]

4.353

5618

\[ {}2 {y^{\prime }}^{3}+y^{\prime } x -2 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

0.503

5619

\[ {}2 {y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0 \]

[_quadrature]

68.356

5620

\[ {}3 {y^{\prime }}^{3}-x^{4} y^{\prime }+2 x^{3} y = 0 \]

[[_1st_order, _with_linear_symmetries]]

83.201

5621

\[ {}4 {y^{\prime }}^{3}+4 y^{\prime } = x \]

[_quadrature]

0.516

5622

\[ {}8 {y^{\prime }}^{3}+12 {y^{\prime }}^{2} = 27 x +27 y \]

[[_homogeneous, ‘class C‘], _dAlembert]

0.739

5623

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+a = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

0.752

5624

\[ {}x {y^{\prime }}^{3}-\left (x +x^{2}+y\right ) {y^{\prime }}^{2}+\left (x^{2}+y+x y\right ) y^{\prime }-x y = 0 \]

[_quadrature]

2.771

5625

\[ {}x {y^{\prime }}^{3}-2 y {y^{\prime }}^{2}+4 x^{2} = 0 \]

[[_1st_order, _with_linear_symmetries]]

135.987

5626

\[ {}2 x {y^{\prime }}^{3}-3 y {y^{\prime }}^{2}-x = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

0.654

5627

\[ {}4 x {y^{\prime }}^{3}-6 y {y^{\prime }}^{2}-x +3 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

1.000

5628

\[ {}8 x {y^{\prime }}^{3}-12 y {y^{\prime }}^{2}+9 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

0.963

5629

\[ {}x^{2} {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+y^{2} y^{\prime }+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

2.415

5630

\[ {}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{3}+b x \left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}-y^{\prime }-b x = 0 \]

[_quadrature]

0.591

5631

\[ {}x {y^{\prime }}^{3}-3 x^{2} y {y^{\prime }}^{2}+x \left (x^{5}+3 y^{2}\right ) y^{\prime }-2 x^{5} y-y^{3} = 0 \]

[‘y=_G(x,y’)‘]

530.461

5632

\[ {}2 x^{3} {y^{\prime }}^{3}+6 x^{2} y {y^{\prime }}^{2}-\left (1-6 x y\right ) y y^{\prime }+2 y^{3} = 0 \]

[[_homogeneous, ‘class G‘]]

12.313

5633

\[ {}x^{4} {y^{\prime }}^{3}-x^{3} y {y^{\prime }}^{2}-x^{2} y^{2} y^{\prime }+x y^{3} = 1 \]

[[_1st_order, _with_linear_symmetries]]

127.410

5634

\[ {}x^{6} {y^{\prime }}^{3}-y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries]]

11.642

5635

\[ {}y {y^{\prime }}^{3}-3 y^{\prime } x +3 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

7.372

5636

\[ {}2 y {y^{\prime }}^{3}-3 y^{\prime } x +2 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

1.521

5637

\[ {}\left (x +2 y\right ) {y^{\prime }}^{3}+3 \left (x +y\right ) {y^{\prime }}^{2}+\left (y+2 x \right ) y^{\prime } = 0 \]

[_quadrature]

5.882

5638

\[ {}y^{2} {y^{\prime }}^{3}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries]]

117.473

5639

\[ {}y^{2} {y^{\prime }}^{3}+2 y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries]]

107.771

5640

\[ {}4 y^{2} {y^{\prime }}^{3}-2 y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries]]

107.145

5641

\[ {}16 y^{2} {y^{\prime }}^{3}+2 y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries]]

105.890

5642

\[ {}x y^{2} {y^{\prime }}^{3}-y^{3} {y^{\prime }}^{2}+x \left (x^{2}+1\right ) y^{\prime }-x^{2} y = 0 \]

[‘y=_G(x,y’)‘]

252.691

5643

\[ {}y^{3} {y^{\prime }}^{3}-\left (1-3 x \right ) y^{2} {y^{\prime }}^{2}+3 x^{2} y y^{\prime }+x^{3}-y^{2} = 0 \]

[‘y=_G(x,y’)‘]

245.719

5644

\[ {}y^{4} {y^{\prime }}^{3}-6 y^{\prime } x +2 y = 0 \]

[[_1st_order, _with_linear_symmetries]]

109.256

5645

\[ {}{y^{\prime }}^{4} = \left (y-a \right )^{3} \left (y-b \right )^{2} \]

[_quadrature]

1.026

5646

\[ {}{y^{\prime }}^{4}+f \left (x \right ) \left (y-a \right )^{3} \left (y-b \right )^{2} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

1.444

5647

\[ {}{y^{\prime }}^{4}+f \left (x \right ) \left (y-a \right )^{3} \left (y-b \right )^{3} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

1.486

5648

\[ {}{y^{\prime }}^{4}+f \left (x \right ) \left (y-a \right )^{3} \left (y-b \right )^{3} \left (y-c \right )^{2} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

3.037

5649

\[ {}{y^{\prime }}^{4}+y^{\prime } x -3 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

2.151

5650

\[ {}{y^{\prime }}^{4}-4 x^{2} y {y^{\prime }}^{2}+16 x y^{2} y^{\prime }-16 y^{3} = 0 \]

[[_homogeneous, ‘class G‘]]

0.630

5651

\[ {}{y^{\prime }}^{4}+4 y {y^{\prime }}^{3}+6 y^{2} {y^{\prime }}^{2}-\left (1-4 y^{3}\right ) y^{\prime }-\left (3-y^{3}\right ) y = 0 \]

[_quadrature]

2.495

5652

\[ {}2 {y^{\prime }}^{4}-y y^{\prime }-2 = 0 \]

[_quadrature]

1.082

5653

\[ {}x {y^{\prime }}^{4}-2 y {y^{\prime }}^{3}+12 x^{3} = 0 \]

[[_1st_order, _with_linear_symmetries]]

3.268

5654

\[ {}3 {y^{\prime }}^{5}-y y^{\prime }+1 = 0 \]

[_quadrature]

0.519

5655

\[ {}{y^{\prime }}^{6} = \left (y-a \right )^{4} \left (y-b \right )^{3} \]

[_quadrature]

1.529

5656

\[ {}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{4} \left (y-b \right )^{3} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

3.841

5657

\[ {}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{5} \left (y-b \right )^{3} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

4.383

5658

\[ {}{y^{\prime }}^{6}+f \left (x \right ) \left (y-a \right )^{5} \left (y-b \right )^{4} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

5.213

5659

\[ {}x^{2} \left ({y^{\prime }}^{6}+3 y^{4}+3 y^{2}+1\right ) = a^{2} \]

[_rational]

16.482

5660

\[ {}2 \sqrt {a y^{\prime }}+y^{\prime } x -y = 0 \]

[[_homogeneous, ‘class G‘], _Clairaut]

1.709

5661

\[ {}\left (x -y\right ) \sqrt {y^{\prime }} = a \left (1+y^{\prime }\right ) \]

[[_homogeneous, ‘class C‘], _dAlembert]

2.796

5662

\[ {}2 \left (1+y\right )^{{3}/{2}}+3 y^{\prime } x -3 y = 0 \]

[_separable]

4.987

5663

\[ {}\sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } = x \]

[_quadrature]

1.050

5664

\[ {}\sqrt {1+{y^{\prime }}^{2}}+a y^{\prime } = y \]

[_quadrature]

1.703

5665

\[ {}\sqrt {1+{y^{\prime }}^{2}} = y^{\prime } x \]

[_quadrature]

1.023

5666

\[ {}\sqrt {a^{2}+b^{2} {y^{\prime }}^{2}}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

7.628

5667

\[ {}a \sqrt {1+{y^{\prime }}^{2}}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

6.301

5668

\[ {}a x \sqrt {1+{y^{\prime }}^{2}}+y^{\prime } x -y = 0 \]

[[_homogeneous, ‘class A‘], _dAlembert]

317.821

5669

\[ {}\sqrt {\left (a \,x^{2}+y^{2}\right ) \left (1+{y^{\prime }}^{2}\right )}-y y^{\prime }-a x = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

78.633

5670

\[ {}a \left (1+{y^{\prime }}^{3}\right )^{{1}/{3}}+y^{\prime } x -y = 0 \]

[_Clairaut]

73.981

5671

\[ {}\cos \left (y^{\prime }\right )+y^{\prime } x = y \]

[_Clairaut]

1.158

5672

\[ {}a \cos \left (y^{\prime }\right )+b y^{\prime }+x = 0 \]

[_quadrature]

0.485

5673

\[ {}\sin \left (y^{\prime }\right )+y^{\prime } = x \]

[_quadrature]

0.529

5674

\[ {}y^{\prime } \sin \left (y^{\prime }\right )+\cos \left (y^{\prime }\right ) = y \]

[_quadrature]

34.034

5675

\[ {}{y^{\prime }}^{2} \left (x +\sin \left (y^{\prime }\right )\right ) = y \]

[_dAlembert]

1.535

5676

\[ {}\left (1+{y^{\prime }}^{2}\right ) \sin \left (-y+y^{\prime } x \right )^{2} = 1 \]

[_Clairaut]

7.965

5677

\[ {}\left (1+{y^{\prime }}^{2}\right ) \left (\arctan \left (y^{\prime }\right )+a x \right )+y^{\prime } = 0 \]

[_quadrature]

1.151

5678

\[ {}{\mathrm e}^{y^{\prime }-y}-{y^{\prime }}^{2}+1 = 0 \]

[_quadrature]

1.320

5679

\[ {}\ln \left (y^{\prime }\right )+y^{\prime } x +a = 0 \]

[_quadrature]

0.681

5680

\[ {}\ln \left (y^{\prime }\right )+y^{\prime } x +a = y \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

1.592

5681

\[ {}\ln \left (y^{\prime }\right )+y^{\prime } x +a +b y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

3.186

5682

\[ {}\ln \left (y^{\prime }\right )+4 y^{\prime } x -2 y = 0 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

2.851

5683

\[ {}\ln \left (y^{\prime }\right )+a \left (-y+y^{\prime } x \right ) = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

1.664

5684

\[ {}a \left (\ln \left (y^{\prime }\right )-y^{\prime }\right )-x +y = 0 \]

[[_homogeneous, ‘class C‘], _dAlembert]

3.296

5685

\[ {}y \ln \left (y^{\prime }\right )+y^{\prime }-y \ln \left (y\right )-x y = 0 \]

[_separable]

3.958

5686

\[ {}y^{\prime } \ln \left (y^{\prime }\right )-\left (x +1\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

2.048

5687

\[ {}y^{\prime } \ln \left (y^{\prime }+\sqrt {a +{y^{\prime }}^{2}}\right )-\sqrt {1+{y^{\prime }}^{2}}-y^{\prime } x +y = 0 \]

[_Clairaut]

11.863

5688

\[ {}\ln \left (\cos \left (y^{\prime }\right )\right )+y^{\prime } \tan \left (y^{\prime }\right ) = y \]

[_dAlembert]

0.378

5689

\[ {}y^{\prime } = \frac {x y}{x^{2}-y^{2}} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

3.469

5690

\[ {}y^{\prime } = \frac {x +y-3}{x -y-1} \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.517

5691

\[ {}y^{\prime } = \frac {2 x +y-1}{4 x +2 y+5} \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.010

5692

\[ {}y^{\prime }-\frac {2 y}{x +1} = \left (x +1\right )^{2} \]

[_linear]

1.537

5693

\[ {}y^{\prime }+x y = x^{3} y^{3} \]

[_Bernoulli]

1.249

5694

\[ {}\frac {2 x}{y^{3}}+\frac {\left (y^{2}-3 x^{2}\right ) y^{\prime }}{y^{4}} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

4.532

5695

\[ {}y+x y^{2}-y^{\prime } x = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.211

5696

\[ {}y^{2} \left (1+{y^{\prime }}^{2}\right ) = R^{2} \]

[_quadrature]

4.911

5697

\[ {}y = y^{\prime } x +\frac {a y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}} \]

[_Clairaut]

34.317

5698

\[ {}y = x {y^{\prime }}^{2}+{y^{\prime }}^{2} \]

[[_homogeneous, ‘class C‘], _rational, _dAlembert]

0.505

5699

\[ {}\left (x +1\right ) y+x \left (1-y\right ) y^{\prime } = 0 \]

[_separable]

1.515

5700

\[ {}y^{2}+x y^{2}+\left (x^{2}-x^{2} y\right ) y^{\prime } = 0 \]

[_separable]

1.728